ANALYSIS OF THE RELATIONSHIP OF TRANSFORMATIONAL LEADERSHIP, WORK ENVIROMENT, AND JOB SATISFACTION ON EMPLOYEE RETENTION OF THE MILLENIAL GENERATION IN THE CREATIVE SECTOR - Rahardianto, Rahardianto; Hadikusumo, Reina A.; Risambessy, Agusthina (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
Millennials now make up a significant portion of the workforce, valuing meaningful work, opportunities for development and a supportive work environment, making these factors crucial in retaining talent in the creative sector. This research aims to analyze the relationship between transformational leadership, work environment, and job satisfaction on the retention of millennial generation employees in the creative sector. The sample in this research consisted of 120 employees who worked in the creative industries in Indonesia who were determined using a purposive sampling approach. Data collection uses a questionnaire instrument which is then distributed online. Data analysis uses the SPSS application by displaying the results of data processing through validity and reliability tests, multiple regression analysis, coefficient of determination and hypothesis testing. Based on the results of data analysis, it is stated that transformational leadership, work environment, and job satisfaction have a positive and significant effect on employee retention. This research highlights the importance of adaptive leadership and a conducive work environment in retaining millennial talent which is vital for maintaining innovation and competitive advantage in the creative sector.